Factors that impact young generation’s consumer preferences for sportswear products in Malaysia / Nur Shakila Saman and Noor Fadzlen Abd Rahman - Saman, Nur Shakila; Abd Rahman, Noor Fadzlen (Faculty of Business and Management, 2014)
This research is to study about factor of country of origin (COO), product quality, style, promotion and brand image towards the consumer preference on young generation for sportswear product. The study was conducted in Malaysia in Kuala Lumpur, Johore and Malacca area. The main problem is the young generation are become wealthier and grow up what they purchase. Young generation are trendier, digitally savvy and exposed to new things. They are willing try new things and difficult to hold them in a brand. Due to the problem, there are certain reasons why the research objective was developed. First, to identify the most factors that will impact young generation consumer preferences on product sportswear. Next, to examine the factor of country of origin (COO), product quality, brand image, style, and promotion toward consumer preferences. The finding stated that all independent variable are positive relationship with consumer preferences. Besides, the result also illustrated that three of the variable which are product quality, brand image and style is has a strong relationship, meanwhile, promotion, country of origin (COO) are at moderate level. Based on finding, there are several recommendation has been suggested to manufacture of sportswear product to help and to improve customer understanding. The manufacture and marketers need to improve and fulfil the need and wants of consumer to build a strong relationship between all factor and consumer preferences.